Investigation of Anti-Cancer Activity of Newly Synthesized 2,4-pentadien-1-one Derivative Containing Benzofuran in Human Lung and Colon Cancer Cells - Erturk, Elif; Tuna, Gonca; Coskun, Demet; Ari, Ferda (Kare Publ, 2023)
Objectives: A member of the flavonoid family, chalcones are natural compounds known to have anticancer effects. Chalcones and their synthetic derivatives have become an important field of interest for cancer research. In this study, we aimed to investigate the anticancer activity of a new Chalcone derivative compound [(2E,4E)-1-(7-ethoxy-1-benzofuran-2-yl)-5-(4-hydroxy-3-methoxyphenyl)penta-2,4-dien-1-one] synthesized by the Claisen-Schmidt reaction based on the curcumin structure in human lung (A549, H1299) and colon cancer (HCT116, HT29) cells. Methods: The effect of Chalcone compound on cell viability was evaluated with the SRB test. In addition, combination studies with 5-FU, which is used as a chemotherapy drug, was performed. The cell death mode was determined by fluorescence imaging method with Hoechst 33342, Annexin-V-FITC and Propidium iodide (PI) triple staining. Results: IC50 values of the Chalcone compound were found as 2.85, 1.46, 0.59, 0.35 mu M for A549, H1299, HCT116, HT29, respectively. As a result of fluorescence imaging, pycnotic nuclei and chromatin condensation were observed in the cells in addition to positive staining with Annexin-V-FITC (green). Conclusion: The results showed that the newly synthesized Chalcone derivative compound has a significant cytotoxic effect on cancer cells and induce apoptosis.
Keywords: Apoptosis; chalcones; neoplasms